Estimulación temprana y su incidencia en el desarrollo de la motricidad fina en niños de educación inicial de la unidad educativa Quinindé, cantón Quinindé, provincia de Esmeraldas, durante el año lectivo 2022 – 2023 - Carrera Carrillo, Cristina Mercedes (2023)
The present research work has as its theme: Early stimulation and its incidence in the development of fine motor skills in children of Initial Education, the problem focuses on the fact that children have not had the opportunity to access early stimulation, which has hindered the development of fine motor skills, consequently the general objective was to strengthen the development of fine motor skills through early stimulation in Initial education I of the "Quinindé" Educational Unit, for which the qualitative approach was used as a methodology , non-experimental, the type of research is documentary bibliographic that allowed the development of a theoretical foundation with different scientific approaches; field because work was done at the scene, for the collection of information the Focus Group was used as a technique with its instrument the question guide that was applied to 6 teachers of the Educational Unit, in the same way the technique was used as the observation with his instrument the observation sheet applied to the 25 boys and girls of Initial education I of the Educational Unit "Quinindé".